2020
DOI: 10.24191/ajue.v16i3.7912
|View full text |Cite
|
Sign up to set email alerts
|

Filipino Teachers' Compartmentalization Ability, Emotional Intelligence, and Teaching Performance

Abstract: Teachers, as individuals outside the classroom, deals with their problems yet are still expected to display desirable dispositions during student interaction. Thus, the strategy for regulating thoughts and emotions is vital for effective teaching. This study aims to measure Filipino teachers' problem compartmentalization ability, their level of emotional intelligence, and teaching performance, mainly when they experienced personal issues. It also seeks to determine the relationship among variables. Validated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Shen (2022) added that being worried and distressed was evident in teachers' physical reactions, and deconstructive feelings such as uncertainty affect their ability to teach. Go et al (2020) emphasized that in the Philippine setting, the Code of Ethics for Professional Teachers and the Philippine Professional Standards for Teachers particularly directed educators to be competent technically and professionally and uphold the dignity and reputation of Filipino teachers. The Asian Journal of University Education (2020) published the silent pressure for Filipino educators to continuously showcase their best abilities to keep up with the dignified image of the profession in society resulting to anxiety or depression.…”
Section: Levels Of Depression Anxiety and Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen (2022) added that being worried and distressed was evident in teachers' physical reactions, and deconstructive feelings such as uncertainty affect their ability to teach. Go et al (2020) emphasized that in the Philippine setting, the Code of Ethics for Professional Teachers and the Philippine Professional Standards for Teachers particularly directed educators to be competent technically and professionally and uphold the dignity and reputation of Filipino teachers. The Asian Journal of University Education (2020) published the silent pressure for Filipino educators to continuously showcase their best abilities to keep up with the dignified image of the profession in society resulting to anxiety or depression.…”
Section: Levels Of Depression Anxiety and Stressmentioning
confidence: 99%
“…The skill to recognize emotion and the awareness of feelings influence the kind of behavior manifested toward oneself and others. Go, et al (2020) also pointed out that every profession has its own unique emotional manifestations. They cited that like in a school setting governed by a set of social rules and norms, emotions must be on check always to maintain the good relationship with colleagues and pupils.…”
Section: Emotional Health Conditions Of Daet North District Teachersmentioning
confidence: 99%
“…In the report of Villanueva (2021), Filipino teachers' commitment has been the major driving force for them to perform their duties and responsibilities despite the pedagogical challenges brought by the pandemic. This scenario leads to a positive disposition, which results in excellent teaching performance (Go et al, 2020).…”
Section: Statistical Treatmentmentioning
confidence: 99%
“…Several studies on teachers' emotional intelligence have already showed that Emotional Intelligence (EI) is important for a good classroom climate (Maamari & Majdalani, 2019;Tsoli, 2015), students' higher academic achievement (Sánchez-Álvarez et al, 2020), teacher engagement (Abiodullah et al, 2020), satisfaction with work (Li et al, 2018) and reducing burn-out (Kant & Shanker, 2021). Moreover, teachers' EI affects their self-efficacy (Kostić-Bobanović, 2020) and their teaching practices (Go et al, 2020;Kaur et al, 2019).…”
Section: Introductionmentioning
confidence: 99%